Respuesta :
The given particular solution is
[tex]y_{p}(t) = ln(1 + 2t) - \frac{1}{2} [/tex]
The ODE is
y'' + 3y = g(t)
Obtain the derivatives of the particular solution.
[tex]y_{p}^{'} = \frac{2}{1+2t} \\\\ y_{p}^{''} = \frac{-4}{(1+2t)^{2}} [/tex]
Because the particular solution should satisfy the ODE, therefore
[tex]g(t)=- \frac{4}{(1+2t)^{2}} +3 \, ln(1+2t)- \frac{3}{2} [/tex]
Answer: [tex]g(t) = - \frac{4}{(1+2t)^{2}} + 3 \, ln(1+2t) - \frac{3}{2} [/tex]
[tex]y_{p}(t) = ln(1 + 2t) - \frac{1}{2} [/tex]
The ODE is
y'' + 3y = g(t)
Obtain the derivatives of the particular solution.
[tex]y_{p}^{'} = \frac{2}{1+2t} \\\\ y_{p}^{''} = \frac{-4}{(1+2t)^{2}} [/tex]
Because the particular solution should satisfy the ODE, therefore
[tex]g(t)=- \frac{4}{(1+2t)^{2}} +3 \, ln(1+2t)- \frac{3}{2} [/tex]
Answer: [tex]g(t) = - \frac{4}{(1+2t)^{2}} + 3 \, ln(1+2t) - \frac{3}{2} [/tex]
Given that [tex]y_{p(t)}=\ln{(1+2t)}, \ \ \ t\ \textgreater \ -\frac{1}{2} [/tex] is a particular solution to the differential equation [tex]y^{\prime\prime}+3y=g(t)[/tex]
Then
[tex][\ln{(1+2t)}]^{\prime\prime}+3[\ln{(1+2t)}]=g(t) \\ \\ \Rightarrow\bold{g(t)= \frac{2(1+6t)}{(1+2t)^2}+3\ln{(1+2t)}}[/tex]
Then
[tex][\ln{(1+2t)}]^{\prime\prime}+3[\ln{(1+2t)}]=g(t) \\ \\ \Rightarrow\bold{g(t)= \frac{2(1+6t)}{(1+2t)^2}+3\ln{(1+2t)}}[/tex]